2006
DOI: 10.1248/bpb.29.585
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Effects of Corosolic Acid in KK-Ay Diabetic Mice

Abstract: Despite considerable progress in the management of diabetes mellitus with synthetic drugs, the search for indigenous natural antidiabetic agents is ongoing. The plant kingdom offers a wide field to search for effective oral hypoglycemics. More than 400 species have been reported to exhibit hypoglycemic effects, but only a few have been investigated. [1][2][3][4][5] The leaf of Banaba (Lagerstroemia speciosa L.) has been used as a traditional Oriental medicine to treat diabetes (polyuria and polydipsia). It con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 9 publications
1
42
0
Order By: Relevance
“…1), a compound which prevents oxidative stress, inflammation, hypertension and so on ( 1 ). The hypoglycemic effect of CA has been reported by various experiments (2)(3)(4)(5). The decrease in insulin resistance due to the increase in GLUT4 translocation has been reported as a mechanism of action ( 6 ).…”
mentioning
confidence: 99%
“…1), a compound which prevents oxidative stress, inflammation, hypertension and so on ( 1 ). The hypoglycemic effect of CA has been reported by various experiments (2)(3)(4)(5). The decrease in insulin resistance due to the increase in GLUT4 translocation has been reported as a mechanism of action ( 6 ).…”
mentioning
confidence: 99%
“…This anti-oxidant effect results from elevated serum glucose. Corosolic acid helps to reduced blood glucose level by activating the transport of glucose across the cell membranes, in short, corosolic acid has insulin-like effect (Liu et al, 2001;Miura et al, 2006;Fukushima et al, 2006). Table II showed that oral administration of extract significantly increased (31.3%, p<0.02) the depressed blood glutathione (a tripeptide of glycine, cystein and glutamic acid, GSH) level of chemically induced diabetic rats.…”
Section: Resultsmentioning
confidence: 96%
“…In Wistar fatty rats, a model for non-insulin-dependent diabetes mellitus, enhanced ACAT activity in the small intestine and hypercholesterolemia were observed when an atherogenic diet containing 1% cholesterol, 0.5% cholic acid, emia. Since excessive plasma insulin levels in KKAy mice decreased after repeated administration of CA (22), improvement in insulin resistance by CA may have reduced blood cholesterol levels and liver cholesterol contents in the long-term. On the other hand, increased cholesterol absorption in the small intestine has been reported in patients with both type 1 and type 2 diabetes (10, 17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Two kinds of specific diet were prepared for this study. One was a high cholesterol diet made of CE-2 (Clea, Japan), 1% cholesterol and 0.5% cholic acid, while the other was the same high cholesterol diet containing 0.023% CA, a dosage similar to that used in previous studies (22,30).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation